2019
DOI: 10.1186/s40462-019-0162-8
|View full text |Cite
|
Sign up to set email alerts
|

Using seasonal landscape models to predict space use and migratory patterns of an arctic ungulate

Abstract: Background Caribou in the Western Arctic Herd undertake one of the longest, remaining intact migrations of terrestrial mammals in the world. They are also the most important subsistence resource for many northern rural residents, who rely on the caribou’s migratory movements to bring them near for harvest. Migratory geography has never been static, but subsistence harvesters have reported recent shifts in migration away from areas where they traditionally occurred. The reasons behind these changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Notably, pregnant females selected calving sites that were characterized by high-quality forage at the average time of peak calving. High fidelity is particularly impressive considering the highly variable winter ranges of individuals in this and other herds (Schaefer et al, 2000;Faille et al, 2010;Peignier et al, 2019), and thus females must routinely travel different routes between winter ranges and the calving area (Kelsall, 1968;Nicholson et al, 2016;Baltensperger and Joly, 2019). Spring FIGURE 5 | Predictive map of high-quality calving habitat for caribou of the Western Arctic Herd, Alaska.…”
Section: Land Covermentioning
confidence: 99%
“…Notably, pregnant females selected calving sites that were characterized by high-quality forage at the average time of peak calving. High fidelity is particularly impressive considering the highly variable winter ranges of individuals in this and other herds (Schaefer et al, 2000;Faille et al, 2010;Peignier et al, 2019), and thus females must routinely travel different routes between winter ranges and the calving area (Kelsall, 1968;Nicholson et al, 2016;Baltensperger and Joly, 2019). Spring FIGURE 5 | Predictive map of high-quality calving habitat for caribou of the Western Arctic Herd, Alaska.…”
Section: Land Covermentioning
confidence: 99%
“…These types of movements can now be examined with more accuracy in paleoecological specimens and used to augment biological models (e.g. Baltensperger and Joly, 2019). Furthermore, major cultural zones of the Yukon-Kuskokwim Delta, the Interior and Arctic Alaska have very distinct 87 Sr/ 86 Sr signals that could be meaningful for understanding trade connection in cultural and archeological materials (Potter et al, 2017(Potter et al, , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of areas farther from existing roads was clearly indicated across both seasons, despite the paucity of roads in the study area. Multiple studies have found that caribou and reindeer may show avoidance or altered movement behavior in proximity to roads (Leblond et al 2013, Panzacchi et al 2013, Wilson et al 2016, Baltensperger and Joly 2019) and that road effects may extend beyond their physical footprint due to noise, dust, human activity, and other factors (Myers‐Smith et al 2006, Shannon et al 2014, Paton et al 2017). While our study finds a negative response to roads during migration, this does not imply that roads pose an absolute barrier.…”
Section: Discussionmentioning
confidence: 99%